Cera de carnaúba em camada sobre filmes e coberturas de fécula de mandioca e seu impacto na vida útil do tomate - Viana, Alcinda Nathally Nogueira (2020)
Amid the environmental problem of plastic waste, as well as the need for packaging, biopolymer films appear as a biodegradable alternative to prolong the shelf life of food. Biopolymeric films based on polysaccharides have good mechanical resistance, however, they are a poor barrier to water vapor because their hydrophilic character. Alternatives to increase its hydrophobicity have been studied, for example, the incorporation by oil/water emulsion is the most used method, but problems such as destabilization of the emulsion and the consequent phase separation can cause an inefficient incorporation. Carnauba wax is highly resistant to the flow of water vapor and is permitted to be used in fruit and other food coatings. Among vegetables, tomatoes stand out as of fundamental importance both in economic and nutritional aspects, being a basic constituent of the human diet. In this context, the present study aims to evaluate different concentrations of saponified carnauba wax deposited as layer on biopolymeric films based on cassava starch, characterizing them, in terms of water vapor permeability, color, opacity, tensile properties and morphological characteristics, as well as its application as tomato coatings, aiming at extending the shelf-life of these fruits. The results showed a reduction in water vapor permeability from 32.6 to 9 g / m²h. Mechanical properties, tensile strength and Young's modulus, were not affected by the addition of the wax layer. The films without wax showed a greater absorption of water. The optical properties showed a greater yellowing and opacity of the films incorporated with wax. Morphologically, the addition of the layer of wax did not promote imperfections. When applied to tomatoes as coating, the treatments with cassava starch and carnauba wax provided greater retention of weight loss, firmness and color compared to the control